Kirigami Reconfigurable Gradient Metasurface. (12th November 2021) - Zheng, Yilin; Chen, Ke; Yang, Weixu; Wu, Linxiao; Qu, Kai; Zhao, Junming; Jiang, Tian; Feng, Yijun
Abstract: Kirigami technique, a method to reconfigure structures via mechanical approaches, has received much attention in material science, due to its versatile and unconventional structural transformations. The counterparts in the electromagnetic metamaterial field has recently allowed for the tunable control of electromagnetic responses. However, they are limited to global tuning of absorption, chirality, etc., leaving much potential of controlling spatially varying distribution and therefore the optical wavefront unexploited. Here, the authors propose a class of kirigami‐based reconfigurable gradient metasurfaces through which the electromagnetic wavefront can be tuned over continuous‐state ranges by changing the meta‐structures from folded (compact) to unfolded (large surface) configurations. As the proof‐of‐concept, meta‐devices including switchable anomalous refractor and reconfigurable metalens are demonstrated both in simulations and experiments. Moreover, a new paradigm to mitigate chromatic dispersion is also realized by the kirigami‐based reconfigurable metalens, which is able to keep the focal length unchanged over a continuous frequency band by setting metalens with various folding states. Their approach provides a new alternative for designing reconfigurable gradient metasurface with additional mechanical properties and may have potential applications in advanced devices such as reconfigurable optical components and imaging system. Abstract : Kirigami‐based reconfigurable gradient metasurface (KRGM) is proposed for the tuning of electromagnetic wavefront by changing the folding pattern of the meta‐structure. The concept is demonstrated both in theory and experiment by a series of passive meta‐devices, which enable functionalities including a switchable anomalous refractor, tunable focusing meta‐lens, and achromatic metalens.